Hubungan Antara Pola Asuh Demokratis dengan Efikasi Diri pada Siswa Kelas XI IPS di SMA N 1 Ranah Batahan - Firdaus Firdaus (Neolectura, 2021)
The purpose of this study is to explain the category of democratic fostering patterns, the category of self-efficacy, and the relationship between democratic parenting patterns and the self-efficacy of students of grade XI IPS at SMA N 1 Ranah Batahan West Pasaman Regency. The research method used is quantitative research method with correlation technique. The population in this study was grade XI students of IPS SMA N 1 Ranah Batahan West Pasaman Regency numbered 119 students with a research sample of 92 students. Withdrawal of research samples using proportional random sampling. The data collection technique in this study is psychological scale, which is guided by the scale of the modified Likert model. The analyst technique used is pearson correlation. The results showed that 85.9% of students had a high democratic parenting pattern and as many as 58.7% of students showed low self-efficacy. The correlation results showed a relationship between democratic parenting patterns and self-efficacy. Effective contribution of democratic fostering pattern to self-efficacy of 22.3%.